JUDICIAL SELF-GOVERNANCE IN SERBIA: CHALLENGES TO AND RESULTS OF A QUANTITATIVE APPROACH - Knežević Bojović, Ana; Ćorić, Vesna (Pravni zapisi, 2024)
Serbia has been continuously changing its judicial regulation landscape since 2000, in an effort to assert judicial independence and judicial self-governance, under strong EU external conditionality. The authors utilize the Judicial Self-Governance Index developed by Šipulová et al. as the main methodological tool aimed to determine whether the achieved level of judicial self-governance in Serbia is consistent with the demands of external conditionality. The research shows that judges control over 50% of relevant competencies, with a gradual increase in judicial self-governance in Serbia during the 2003–2023 period. This is consistent with the external conditionality demands and with the de iure implementation of the judicial council model. The research also points to some limitations of the applied methodology and highlights the need for a comprehensive examination of de facto judicial self-governance, while giving due regard to all integral parts of the complex rule of law principle.
Keywords: Judges; Judicial Self-governance,; Judicial Council; Judicial Self-Governance Index; Rule of Law; European Union; External Conditionality; Serbia